Development of Infrastructure, Social and Economy at Developing Village - Durratun Nashihah; Dian Lovitasari (Department of Public Administration, 2023)
To increase a nation's prosperity, development must take into account three key factors. Initially, let's look at infrastructure. Infrastructure is crucial in boosting economic growth, with locations with enough infrastructure showing faster growth. The descriptive and qualitative approaches used in this study have the following two research focuses: infrastructure, society, and economy development in a village. The findings of this study show that infrastructure, social, and economic development in developing villages have not been adequately implemented and compatible. The areas where it is not completely implemented and compatible are those related to the construction of infrastructure, such as schools and road amenities. Lack of budgeting and communication issues between village heads and village officials when submitting the development program are to blame for some road facility building delays.